The role and mechanism of the gut microbiota in the development and treatment of diabetic kidney disease - Wu, Xiaofang; Zhao, Lei; Zhang, Yujiang; Li, Kailong; Yang, Jurong (Frontiers in Physiology, 2023)
Diabetic kidney disease (DKD) is a common complication in patients with diabetes mellitus (DM). Increasing evidence suggested that the gut microbiota participates in the progression of DKD, which is involved in insulin resistance, renin-angiotensin system (RAS) activation, oxidative stress, inflammation and immunity. Gut microbiota-targeted therapies including dietary fiber, supplementation with probiotics or prebiotics, fecal microbiota transplantation and diabetic agents that modulate the gut microbiota, such as metformin, glucagon-like peptide-1 (GLP-1) receptor agonists, dipeptidyl peptidase-4 (DPP-4) inhibitors, and sodium-glucose transporter-2 (SGLT-2) inhibitors. In this review, we summarize the most important findings about the role of the gut microbiota in the pathogenesis of DKD and the application of gut microbiota-targeted therapies.